Application of epineural sheath conduit for restoration of 6‐cm long nerve defects in a sheep median nerve model. Issue 4 (4th December 2018) - Siemionow, Maria; Cwykiel, Joanna; Uygur, Safak; Kwiecien, Grzegorz; Oztürk, Can; Szopinski, Jacek; Madajka, Maria
Abstract : Background: Due to limited number of studies, we tested feasibility of autologous epineural sheath conduit (ESC) in repair of 6‐cm median nerve gaps in a sheep—the large animal model. Materials and methods: Eight ewes, 6–8 months old, 30–35 kg, were divided into three experimental groups: group 1—no defect repair ( n  = 4 nerves/group), group 2—autograft controls ( n  = 6 nerves/group), group 3—autologous ESC filled with saline ( n  = 6 nerves/group). ESC was constructed from a 6‐cm long segment of sheep median nerve and tested for expression of laminin B, Glial fibrillary acidic protein (GFAP), S‐100 and CD31 using immunofluorescent staining. At 6 months after nerve repair, nerve conduction velocity and somatosensory evoked potentials (SSEP) assessed neurosensory recovery, while histomorphometry tested nerve regeneration. Results: Ex vivo characterization of ESC, before in vivo nerve gap repair, showed high laminin B expression, which supports axonal growth. At 6 months post‐repair, structural integrity of ESC was preserved. ESC was well‐vascularized and tissue adhesions were comparable to autograft controls. The maximal conduction velocities (29.80 ± 5.85 ms vs. 32.28 ± 6.75 ms; p  = .44), action potential amplitudes (32.68 ± 17.44 mV vs. 44.14 ± 23.10 mV; p  = .38) and SSEP amplitude values (6.18 ± 5.84 mV vs. 4.68 ± 2.53 mV; p  = .28) were comparable between autograft and ESC groups. Presence of regenerating axons was confirmed in the distal segment of ESC at 6 months after repair. Conclusion: The feasibility of ESC in restoration of 6‐cm long nerve defects in a sheep median nerve model was confirmed by nerve conduction assessments and correlated with axonal regeneration tested by histomorphometry. We confirmed ESC potential in support of regeneration of long nerve defects.